Analisis Kebutuhan E-Modul Berbasis Canva Pada Materi Sistem Saraf - Sendy Dwi Maulandika; Dwi Candra Setiawan (IKIP Budi Utomo Malang, 2023)
Development of technology-based teaching materials at this time is very necessary. Teachers must be creative and innovative in developing teaching materials, especially technology-based teaching materials. This study aims to determine the needs of students in obtaining technology-based teaching materials.This research is a development research. where in this initial research only a needs analysis was carried out which was used as the basis for the stages of the 4D model development. This research was conducted at SMA Panjura Malang in May with 11th grade students.Based on the results of the distribution of the questionnaire, data obtained from 100% teacher responses and 100% student responses agreed to develop Canva-based e-module teaching materials on nervous system material.Based on the research results, it can be concluded that it is necessary to develop a technology-based teaching material to support the learning process.